Indian Hand Anthropometry: Computer Tomography-Based Morphometric Analysis of Metacarpal - Reddy, Maryada Venkateshwar; G., Mithun Pai; Kumar, Morum Mahendra; Bhat, Anil K.; Annapareddy, Adarsh; Thatte, Mukund R. (Indian Journal of Plastic Surgery, 2024)
Introduction Metacarpal fractures are common and have various treatment options, but understanding their morphometry is crucial for optimizing fixation techniques and reducing complications. Accurate assessment of metacarpal anatomy is challenging in conventional radiographs but feasible with computed tomography (CT) scans, which offer precise views. This study aimed to provide accurate anatomical data on metacarpals within an Indian population using CT scans and to compare the results with existing literature. The findings have implications for surgical procedures, including plating, pinning, and intramedullary screw fixation.Materials and Methods This retrospective analysis utilized CT scans of 100 hands, including 50 males and 50 females, from two hospitals in India. Inclusion criteria included complete metacarpal visualization with a slice thickness of 0.6 mm, while exclusion criteria involved trauma, deformity, or underlying pathologies. Various parameters of all metacarpals were measured using RadiAnt DICOM Viewer 2021.1, providing accurate anteroposterior and lateral views.Results Male and female cohorts had mean ages of 38.58 ± 12.02 and 43.60 ± 13.61 years, respectively. The study showed good to excellent reliability in measurements. The 2nd metacarpal was consistently the longest, and the general length pattern was 3rd > 4th > 5th > 1st metacarpal in both genders. Men generally had larger metacarpal dimensions than women, except for intramedullary diameter, which showed minimal sex-related differences. Notably, the medullary cavity's narrowest part was at the 4th metacarpal, and the thumb had the widest intramedullary diameter.Conclusion This study provides valuable anatomical reference data for metacarpals in an Indian population, aiding in optimizing surgical techniques for metacarpal fractures. The 2nd metacarpal consistently stood out as the longest, and men generally had larger metacarpal dimensions than women. These insights into anatomical variations can inform clinical decisions and stimulate further research in this field. However, a larger and more diverse sample would enhance the study's representativeness.
Keywords: metacarpals; metacarpal fractures; CT scans; Indian population; morphometry; normative data